Measuring the Performance of a Dehydration Plant of Apples - Sánchez Ramírez, Rodrigo Antonio; Vincent, Charles; González Araya, Marcela; Paliza, Juan Carlos (CENTRUM Publishing, 2015)
Given the importance of the Chilean dried-fruit market and the characteristics of the industrial process of dehydration, it becomes imperative for companies to measure the efficiency of their production processes in order to identify critical areas and take the necessary actions to improve them. Hence, the present work performs an efficiency analysis for the production of dried apples in a plant of the Maule region, Chile. The methodology used is Data Envelopment Analysis, considering both discretionary and non-discretionary variables. The results indicate that the application of the model without non-discretionary variables shows higher efficiency indices than the model with non-discretionary variables. Additionally, the efficiency analysis results, segregated by variety, origin, and fruit type, indicate that the selection of these segregations could be used to increase the production or generate higher efficiencies. Finally, the technological change in the same plant is analysed through the Malmquist index. The findings of this research could help improve the decision-making process of managers concerned with the efficient use of resources within the company.
Keywords: Performance; Productivity; Efficiency Analysis; Processed Food Industry; Dried Apples; Data Envelopment Analysis.; http://purl.org/pe-repo/ocde/ford#5.02.04